Pelatihan Penulisan Naskah Ilmiah Jurnal Investigasi Bagi Guru-Guru Se-Kota Tangerang Selatan - Gatot Kusjono; Suprianto Suprianto; Ali Maddinsyah; Syamruddin Syamruddin; Sugeng Widodo (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
Community service activities. Scientific Manuscript Writing Training Journal of Educational Research at SMP Negeri 17 Tangerang Selatan aims to help elementary/junior/junior high school teachers in South Tangerang City in writing scientific manuscripts that will be published in ISSN journals. The training method is carried out using the method of mentoring, discussion, workshops and technical guidance (bimtek) of writing scientific manuscripts in accordance with journal manuscript standards. The results of the training were obtained as many as 11 elementary school teacher manuscripts (73%) and 4 junior high school teacher manuscripts (27%) published in the INVESTIGATION journal of SMP Negeri 17 Tangerang Selatan Volume 2 Number 2 Month September 2021 - December 2022. Publishing teacher scientific manuscripts in the INVESTIGATION journal is certainly very important. assisting teachers in fulfilling their obligations to journalize their scientific texts, so that they are not constrained in promotion of class or position. The targeted output in this community service activity is the publication of the results of community service activities in national scientific journals with ISSN.